Effect of geogrid on dry-shrinkage cracking of loess - Guo, Hong; Yang, Kuibin; Wang, Shaofei; Guo, Chen; Nan, Yalin; Tao, Mingjiang (Frontiers in Earth Science, 2023)
In this paper, an experimental approach is employed to investigate the reinforcing impact of geogrids on the dry-shrinkage cracking of loess. At various evaporation temperatures and for varying specimen thicknesses, the evolution of the surface fissures induced in the loess samples with and without geogrids was monitored and analyzed. According to the findings, the evaporation rate of the samples increased when the evaporation temperature was increased, and the thickness of the samples was reduced under the same conditions. At higher temperatures, geogrids had a substantial impact on reducing the evaporation rate and suppressing the dry-shrinkage cracks. The occurrence and development of the dry-shrinkage cracks of loess are divided into three stages: the formation stage, the acceleration stage, and the stabilization stage. The ratio of the number of cracks to the number of fracture nodes in the reinforced soil was lower than that of the unreinforced soil. This ratio changed further with the sample thickness. The geogrids can effectively reduce the evaporation rate of water and the development rate of the dry-shrinkage cracks in loess. Consequently, the crack distribution in the loess samples is uniform and prevents the formation of large and long cracks. Using a 3D discrete element model, it is feasible to simulate the loess before and after the geogrid reinforcement.